Polyazulene sulfide anion exchange membrane as well as preparation method and application thereof
By using polysaccharide sulfide polymer to prepare an alkali anion exchange membrane with strong dipole azoyl groups and sulfur-containing backbone, the problems of low ion conductivity and poor alkali stability of AEM are solved, and the comprehensive improvement of high conductivity, mechanical strength and alkali stability are achieved. It is suitable for alkaline fuel cells and electrolytic cells.
Patent Information
- Application Number
- CN202411902018.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-23
AI Technical Summary
In the prior art, the AEM ion conductivity of the anion exchange membrane fuel cell and the alkaline electrolytic cell has low AEM ion conductivity and poor alkali stability, resulting in a decrease in the mechanical properties of the membrane and a shortened service life.
A polysaccharide sulfide polymer is used as the main component of the film, and an alkali anion exchange membrane with strong dipole azoyl groups and sulfur-containing backbone is formed by polymerization and quaternization treatment. The membrane improves mechanical strength through branched structure, reduces water absorption and swelling, and improves alkaline stability through high-stability cationic groups and nucleophilic oxalyl groups.
It has achieved high OH-conductivity (OH-conductivity >100mS cm-1 at 80°C), high mechanical strength (tensile strength >35MPa, elongation at break >10%) and good alkaline stability (maintained at 80°C and 1M KOH for >500h), and is suitable for alkaline fuel cells and alkaline electrolytic cells.
Smart Images

Figure CN119751871A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of membrane technology, and in particular to a polyazulene sulfide anion exchange membrane and a preparation method and application thereof. Background Art
[0002] Due to global development and population growth, energy demand continues to grow rapidly worldwide. Green hydrogen can be produced by water electrolysis technology driven by overcapacity "wasted solar power, abandoned wind power and abandoned electricity", and fuel cells are the main application direction of hydrogen energy. At present, proton exchange membrane fuel cells and acidic electrolyzers operating under acidic conditions require the use of precious metal catalysts and expensive proton exchange membranes. The cost of producing and utilizing hydrogen is too high, and industrial development has been greatly hindered. Anion exchange membrane fuel cells and alkaline water electrolysis technology can use low-alkaline electrolytes and non-precious metal catalysts, which greatly reduces operating costs, and therefore have received widespread attention.
[0003] Anion exchange membrane (AEM) is a key component of anion exchange membrane fuel cells and alkaline electrolyzers. It is crucial to prepare anion exchange membranes with high hydroxide conductivity and stable chemical properties, so as to achieve high power density and long-term durability of anion exchange membrane fuel cells and alkaline electrolyzers. AEM is composed of a polymer skeleton, cationic groups and mobile ions. The properties of the polymer backbone structure and cationic groups directly determine the performance of AEM. The research on AEM currently still faces the following technical bottlenecks: (1) Due to OH - The radius is H + The radius is large, and the OH in AEM - The conductivity is only the H + The conductivity of the membrane is 20% to 33%. However, the most direct way to increase the conductivity is to increase the ion exchange capacity (IEC). The increase in IEC means that more hydrophilic cationic groups need to be introduced, which will increase the water absorption rate of the membrane and increase the swelling, thereby causing the mechanical properties of the membrane to decrease. Therefore, solving the "trade-off" effect between the ionic conductivity and dimensional stability of the membrane is crucial to the development of AEM. (2) Under hot alkaline working conditions, the polymer skeleton and cationic groups are susceptible to nucleophilic OH - The attack by ions causes complex degradation reactions of the main chain structure and cationic groups, which degrades the membrane performance and even reduces the service life of the AEM.
[0004] Therefore, improving the alkaline stability of AEM and extending the service life of the membrane are issues that need to be addressed urgently. Summary of the invention
[0005] In order to solve the above-mentioned technical problems existing in the prior art, the present application provides a polyazulene sulfide anion exchange membrane and a preparation method and application thereof, so as to overcome the problems of low ion conductivity and poor alkali stability of AEM in the prior art.
[0006] In order to achieve the above purpose, the technical solution of the embodiment of the present application is:
[0007] The first aspect of the present application provides a polyazulene sulfide anion exchange membrane, wherein the polyazulene sulfide anion exchange membrane contains a polyazulene sulfide polymer and has the following structure:
[0008]
[0009] Wherein, R1 is a cationic group, R2 is a branching group, a is any integer between 1 and 10,000, and b is any integer between 0 and 10,000.
[0010] In combination with the first aspect, preferably, the R1 is at least one of the following structures:
[0011]
[0012] Wherein, n is an integer greater than or equal to 0.
[0013] In combination with the first aspect, preferably, the R2 is at least one of the following structures (matching the R2 in the above general formula one by one according to the number of connecting bonds):
[0014]
[0015]
[0016]
[0017] The second aspect of the present application provides a method for preparing the polyazulene sulfide anion exchange membrane according to the first aspect, the preparation method comprising:
[0018] (1) Preparation of polyazulene sulfide polymer:
[0019] Na2S, an azulene monomer A as shown in Formula 1, and a branched monomer R2-Br are placed in a reaction kettle, dissolved in a first organic solvent, rapidly heated, reacted, and then the solid product is washed, dried, and collected; the product is dissolved in a second organic solvent, potassium carbonate and iodomethane are added, reacted in the dark, and then ethyl acetate is added, purified, and the polyazulene sulfide polymer is collected;
[0020]
[0021] (2) Preparation of polyazulene sulfide anion exchange membrane:
[0022] The polyazulene sulfide polymer is dissolved in a second organic solvent, and then dried and collected. - type film, so that the I - Type membrane for ion exchange to obtain OH - type membrane, and after purification, the polyazulene sulfide anion exchange membrane was collected.
[0023] In combination with the second aspect, preferably, the molar ratio of the sum of the added amounts of the azulene monomer and the branched monomer to the added amount of the Na2S is 1:0.9-1.5.
[0024] In combination with the second aspect, preferably, the reaction temperature is greater than 150° C. and the reaction time is greater than 4 hours.
[0025] In combination with the second aspect, preferably, the first organic solvent is one or more of dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide.
[0026] In combination with the second aspect, preferably, the second organic solvent is one or more of acetonitrile, tetrahydrofuran, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone and sulfolane.
[0027] The third aspect of the present application provides a polyazulene sulfide anion exchange membrane as described in the first aspect, and use of the polyazulene sulfide anion exchange membrane prepared by the method as described in the second aspect in preparing alkaline fuel cells and alkaline electrolytic cells.
[0028] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:
[0029] The polyazulene sulfide anion exchange membrane provided in the embodiment of the present application is a basic anion exchange membrane prepared by polymerization and quaternization, wherein the strong dipole moment azulene group and the sulfur-containing main chain promote the formation of a strengthened hydrogen bond network, promoting OH - The branched structure produces high mechanical strength, greatly reducing the water absorption and swelling rate of the anion exchange membrane, thereby improving dimensional stability; at the same time, the high stability cationic group and nucleophilic azulenyl group increase its alkaline stability, and its high OH - The electrical conductivity, alkaline stability and high mechanical strength indicate that the polyazulene sulfide anion exchange membrane prepared in the present application can be used as anion exchange membrane material for alkaline fuel cells and alkaline electrolytic cells.
[0030] The polyazulene sulfide anion exchange membrane provided in this application has high OH - Electrical conductivity (80℃, OH - Conductivity>100mS cm -1), high mechanical strength (tensile strength>35MPa, elongation at break>10%), high dimensional stability, good processability, and excellent alkaline stability in 1M KOH at 80°C (>500h).
[0031] Compared with other types of branched poly(aryl-piperidine) anion exchange membranes, the strong dipole moment azulene groups and sulfur-containing main chains in its molecular structure contribute to the formation of a strengthened hydrogen bond network, promoting OH - The introduction of nucleophilic azulenyl groups makes the structure less susceptible to OH - attack, enhancing its alkaline stability; the formation of branched structure makes the molecular chains entangled with each other, enhancing its mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The synthetic route diagram of 6-6'-biazulene cross-linked poly 6-piperidinylazulene sulfide (b-PAS-6Pip-BiAz) provided in this application
[0033] Figure 2 This is the synthesis route diagram of b-PAS-6pip-3AzPh provided in this application.
[0034] Figure 3 The synthetic route diagram of poly 6-piperidinylazulene sulfide (PAS-6pip) provided in this application.
[0035] Figure 4 The polyazulene sulfide anion exchange membrane OH prepared in Examples 1, 2 and 3 - Conductivity test results.
[0036] Figure 5 These are the anion exchange membrane water electrolysis test results of the polyazulene sulfide anion exchange membranes prepared in Examples 1, 2 and 3. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings. The described embodiments should not be regarded as limiting the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of this application.
[0038] In the following description, reference is made to "some embodiments", which describe a subset of all possible embodiments, but it is understood that "some embodiments" may be the same subset or different subsets of all possible embodiments, and may be combined with each other without conflict. Unless otherwise defined, all technical and scientific terms used in the embodiments of the present application have the same meaning as those commonly understood by those skilled in the art of the technical field of the embodiments of the present application. The terms used in the embodiments of the present application are only for the purpose of describing the embodiments of the present application and are not intended to limit the present application.
[0039] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.
[0040] It should be noted that all raw materials / reagents in the examples of the present application can be purchased on the market or prepared according to conventional methods well known to those skilled in the art; the term "and / or" in the examples of the present application is only used to describe the association relationship between associated objects, indicating that three relationships may exist, for example, A and / or B means the existence of A alone, B alone, and A and B at the same time, wherein A and B may be singular or plural, and the character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0041] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0042] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0043] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0044] Those skilled in the art will appreciate that the numerical ranges in the examples of the present application are to be understood as also specifically disclosing each intermediate value between the upper and lower limits of the range. Each smaller range between the intermediate values in any stated value and stated range and any other stated value or intermediate value in the range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.
[0045] Unless otherwise stated, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art in the field described in the present application. Although the present application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the embodiments or test cases of the present application. All documents mentioned in this specification are generally incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of the present application shall prevail.
[0046] It should be noted that all raw materials and / or reagents in the examples of the present application are purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0047] The following are the test methods used in the examples:
[0048] Performance Test:
[0049] The equipment and testing methods involved in the embodiment are as follows:
[0050] Ion exchange capacity (IEC) test method: Take the Cl - Type or Br - The film was dried in a vacuum oven at 75°C and weighed, and the weight of the dry film was recorded. The dry film was soaked in 25 mL of 0.2 M NaNO3 solution for 6 hours, repeated three times, and the NaNO3 solution after ion exchange was collected. The indicator potassium chromate solution was added to the solution, and titrated with 0.01 M AgNO3 standard solution. When a brick-red precipitate appears and does not disappear after shaking, the titration is complete. Record the volume of AgNO3 solution consumed. The product of the concentration and volume of the AgNO3 solution divided by the mass of the dry film is the IEC.
[0051] OH -Conductivity test: The electrochemical workstation used is produced by Shanghai Chenhua Instrument Co., Ltd., model CHI660E. The conductivity of the membrane at different temperatures was tested by the alternating current impedance method (EIS). The measured potential amplitude was 10mV. In order to reduce the error caused by the contact resistance to the measurement results, the resistance tested was the in-plane resistance of the membrane sample. In the experiment, the membrane was cut into a size of 40mm×10mm, placed in a fixture, and the fixture was placed in pure water. The test temperature was from 30℃ to 80℃, and the membrane resistance was tested every 10℃. It was necessary to keep warm for 1h before the test. Finally, the ionic conductivity σ of the sample was calculated according to the formula: σ=l / (wdR), where l is the length of the membrane between the electrodes (cm), w is the width of the membrane (cm), d is the thickness of the membrane (μm), and R is the measured membrane resistance (mΩ).
[0052] Anion exchange membrane water electrolysis performance test: anode is loaded with IrO2 (1mg / cm 2 ) titanium felt, the cathode is loaded with 10wt% Pt / C (1mg / cm 2 ) carbon paper, the electrode area is 4cm 2 The MEA electrolytic cell was assembled, the electrolyte was 1M KOH, the circulation rate was 20mL / min, and the test temperature was 60°C. The test instrument was CHI660e, and the electrolytic cell was subjected to a 0-2.5V linear voltammetric sweep test.
[0053] Tensile strength test: Instron M3300 electronic universal testing machine was used to test the dry film sample 5×0.5 cm, with a tensile rate of 5 mm / min.
[0054] Alkaline stability test: The prepared anion membrane was immersed in NaOH solutions of different temperatures and concentrations, and its conductivity was measured at the same time. The alkaline stability was analyzed by the change in the conductivity of the electrolyte membrane. The alkaline stability time was defined as the time when the conductivity remained 90% of the initial conductivity after being immersed in 1M KOH at 80°C.
[0055] Swelling rate test: After vacuum drying at 80°C, record the dry weight (W dry ) and length (L dry Then, the samples were immersed in degassed deionized water for 12 h at different temperatures. After wiping off excess water from the surface, the wet weight of the samples (W wet ) and length (L wet ). The water content and swelling degree can be calculated by the following formula:
[0056]
[0057] In a first aspect, an embodiment of the present application provides a polyazulene sulfide anion exchange membrane, wherein the polyazulene sulfide anion exchange membrane contains a polyazulene sulfide polymer and has the following structure:
[0058]
[0059] Wherein, R1 is a cationic group, R2 is a branched group, a is any integer between 1 and 10,000, and b is any integer between 0 and 10,000.
[0060] The polyazulene sulfide anion exchange membrane provided in the embodiment of the present application is a basic anion exchange membrane prepared by polymerization and quaternization, wherein the strong dipole moment azulene group and the sulfur-containing main chain promote the formation of a strengthened hydrogen bond network, promoting OH - The branched structure produces high mechanical strength, greatly reducing the water absorption and swelling rate of the anion exchange membrane, thereby improving dimensional stability; at the same time, the high stability cationic group and nucleophilic azulenyl group increase its alkaline stability, and its high OH - The electrical conductivity, alkaline stability and high mechanical strength indicate that the polyazulene sulfide anion exchange membrane prepared in the present application can be used as anion exchange membrane material for alkaline fuel cells and alkaline electrolytic cells.
[0061] In a specific embodiment, R1 in the embodiment of the present application is preferably one of the following structures:
[0062]
[0063] Wherein, n is an integer greater than or equal to 0.
[0064] In a specific embodiment, R2 in the embodiment of the present application is preferably one of the following structures:
[0065]
[0066]
[0067]
[0068]
[0069] In a second aspect, an embodiment of the present application provides a method for preparing the polyazulene sulfide anion exchange membrane according to the first aspect, the preparation method comprising:
[0070] (1) Preparation of polyazulene sulfide precursor:
[0071] Na2S, an azulene monomer A as shown in Formula 1, and a branched monomer R2-Br are placed in a reaction kettle, dissolved in a first organic solvent, rapidly heated, reacted, and then the solid product is washed, dried, and collected; the product is dissolved in a second organic solvent, potassium carbonate and iodomethane are added, reacted in the dark, and then ethyl acetate is added, purified, and the polyazulene sulfide polymer is collected;
[0072]
[0073] (2) Preparation of polyazulene sulfide anion exchange membrane:
[0074] The cationic polyazulene sulfide is dissolved in a third organic solvent, and the resulting mixture is collected. - type film, so that the I - Type membrane for ion exchange to obtain OH - type membrane, and after purification, the polyazulene sulfide anion exchange membrane was collected.
[0075] It should be noted that the polyazulene sulfide precursor in the embodiment of the present application is prepared in the following manner: first, an azulene monomer, a branched monomer and Na2S are placed in a reaction kettle in a certain proportion, dissolved in a first organic solvent to obtain a mixed solution, the mixed solution is rapidly heated, and after a certain reaction time, the obtained solid product is collected, and the polymer solid is washed with deionized water and ethanol and dried to obtain polyazulene sulfide.
[0076] It should be noted that in the embodiments of the present application, collecting the polyazulene sulfide polymer includes: filtering to obtain a solid polymer, washing it three times with deionized water, washing it once with anhydrous ethanol, and vacuum drying it.
[0077] There is no particular limitation on the drying conditions in the present application, as long as a product of constant weight can be obtained. In the examples of the present application, the drying temperature is preferably 80° C. and the drying time is preferably 24 h.
[0078] It should be noted that in the examples of the present application, the reaction was carried out at room temperature with stirring for 24 hours in the dark.
[0079] It should be noted that in the examples of the present application, the N atom in the azulene monomer reacts with methyl iodide to form a quaternary ammonium cation.
[0080] It should be noted that ethyl acetate in the examples of the present application serves as a good solvent for methyl iodide and can dissolve unreacted monomers. It also serves as a poor solvent for the polymer and causes the polymer to precipitate, thereby purifying the polymer.
[0081] In a specific embodiment, the molar ratio of the azulene monomer to the branched monomer in the embodiment of the present application is preferably 0-99:1.
[0082] Among them, when the molar ratio of the azulene monomer to the branching monomer is greater than 99:1, that is, when the content of the branching monomer is too low, the effect of the branching monomer on improving the performance of the anion exchange membrane is weak.
[0083] In a specific embodiment, the molar ratio of the sum of the added amounts of the branched monomer and the azulene monomer to the added amount of Na2S in the embodiment of the present application is preferably 1:0.9-1.2.
[0084] In a specific embodiment, the molar ratio of the sum of the added amounts of the branched monomer and the azulene monomer to Na2S in the embodiment of the present application is preferably 1:0.9-1.5.
[0085] Among them, when the molar ratio of the sum of the added amounts of branched monomers and azulene monomers to Na2S is less than 1:1.2, the local polymerization rate will be too fast, resulting in a too wide molecular weight distribution; when the molar ratio of the sum of the added amounts of branched monomers and azulene monomers to Na2S is greater than 1:0.9, the reaction yield and rate will decrease.
[0086] In a specific embodiment, the first organic solvent in the embodiment of the present application is preferably one of dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide.
[0087] The first organic solvents are used to dissolve the reactants.
[0088] In a specific embodiment, the second organic solvent in the embodiment of the present application is preferably one of acetonitrile, tetrahydrofuran, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide and cyclopentane.
[0089] The second organic solvents play a role in dissolving the polymer.
[0090] In a third aspect, embodiments of the present application provide a polyazulene sulfide anion exchange membrane as described in the first aspect, and use of the polyazulene sulfide anion exchange membrane prepared by the method as described in the second aspect in preparing alkaline fuel cells and alkaline electrolytic cells.
[0091] In a specific embodiment, the OH of the polyazulene sulfide anion exchange membrane of the present application embodiment at 80°C - The conductivity is preferably at least 100 mS / cm.
[0092] The technical method of the present application will be further described below in conjunction with specific embodiments.
[0093] Example 1
[0094] This embodiment 1 provides a method for preparing a 6-6'-biazulene cross-linked poly-6-piperidinylazulene sulfide anion exchange membrane, namely, a b-PAS-6Pip-BiAz anion exchange membrane, and the specific steps are as follows:
[0095] (1) According to the literature method (Journal of Organic Chemistry 2019, 84(3), 1257-1275; Tetrahedron 2006, 62(48), 11227-11239), the monomer 6-(N-piperidinyl)-1,3-dibromoazulene and the monomer 1,3,1',3'-tetrabromo-6,6'-azulene were prepared.
[0096] Weigh anhydrous Na2S (245 mg), 6-(N-piperidinyl)-1,3-dibromoazulene (1 g), 1,3,1',3'-tetrabromo-6,6'-azulene (81 mg), and NaOH (20 mg) and place them in a reactor, and add 20 mL of N-methylpyrrolidone (NMP). Rapidly heat to 200 ° C and react for 6 hours. After cooling naturally, wash with deionized water and anhydrous ethanol. The product obtained after filtration is vacuum dried at 80 ° C for 8 hours. The dried product is a black solid powder, a total of 0.7 g, with a yield of 94%. Dissolve 1 g of the product in 30 mL of dimethyl sulfoxide (DMSO), then add K2CO3 (0.39 g) and iodomethane (1 mL), and stir the reaction at room temperature in the dark for 24 hours. Add 100 mL of ethyl acetate to the viscous solution obtained. The light yellow precipitate was filtered, washed with water three times, and dried in an oven at 80°C under vacuum for 24 h to obtain b-PAS-6Pip-BiAz. The chemical structure of the polymer was determined by NMR and IR characterization. Figure 1 As shown, the weight average molecular weight is 7.3×10 5 , wherein a is an integer of 0-10000, b is an integer of 0-200, and the polymerization mode of the groups in brackets corresponding to ab is random polymerization.
[0097] In order to facilitate the understanding of the synthesis process of the above-mentioned 6-6'-biazulene cross-linked poly 6-piperidinylazulene sulfide (b-PAS-6Pip-BiAz), the present application provides a synthesis route diagram of 6-6'-biazulene cross-linked poly 6-piperidinylazulene sulfide (b-PAS-6Pip-BiAz), as shown in FIG. Figure 1 As shown, Figure 1 This is a synthetic route diagram of 6-6' biazulene cross-linked poly 6-piperidinylazulene sulfide (b-PAS-6Pip-BiAz) provided in this application.
[0098] (2) Preparation of poly-6-piperidinazulene sulfide anion exchange membrane:
[0099] b-PAS-6Pip-BiAz (1 g) was dissolved in 30 mL DMSO, and the polymer solution was filtered through a 0.45 μm polytetrafluoroethylene filter membrane, and the membrane solution was cast on a clean glass plate. Subsequently, the solution was evaporated at 80 ° C for 12 h, evaporated at 120 ° C for 12 h, and vacuum dried at 120 ° C for 24 h to completely remove the residual solvent. A dense I-type membrane was peeled off from the glass plate. In 1M KCl solution, ion exchange was performed at 80 ° C for 12 h, and then washed with deionized water 3 times to remove residual salts to obtain Cl - The membrane was placed in 1M KOH solution at 80°C for 12 h for ion exchange, and then washed three times with deionized water under nitrogen atmosphere to obtain OH - type membrane, namely b-PAS-6Pip-BiAz anion exchange membrane.
[0100] Example 2
[0101] This embodiment 2 provides a method for preparing a polyazulene sulfide anion exchange membrane, namely, a triazulene cross-linked poly 6-piperidinylazulene sulfide (b-PAS-6pip-3AzPh) anion exchange membrane, and the specific steps are as follows:
[0102] (1) According to the literature method (Journal of Organic Chemistry 2019, 84 (3), 1257-1275; Tetrahedron 2004, 60 (25), 5357-5366), the monomer 6-(N-piperidinyl)-1,3-dibromoazulene and the monomer 1,3,5-tri(2-azulene)benzene were prepared. Anhydrous Na2S (232 mg), 6-(N-piperidinyl)-1,3-dibromoazulene (1 g), 1,3,5-tri(2-azulene)benzene (99 mg), and NaOH (20 mg) were weighed and placed in a reaction kettle, and 20 mL of N-methylpyrrolidone (NMP) was added. The temperature was quickly raised to 200 °C and the reaction was carried out for 6 h. After cooling naturally, the mixture was washed with deionized water and anhydrous ethanol. The product obtained after filtration was vacuum dried at 80 °C for 8 h. The dried product is a black solid powder, 0.7 g in total, with a yield of 95%. 1 g of the product was dissolved in 30 mL of dimethyl sulfoxide (DMSO), and then K2CO3 (0.39 g) and iodomethane (1 mL) were added, and the reaction was stirred at room temperature in the dark for 24 h. Ethyl acetate was added to the obtained viscous solution. After filtering the light yellow precipitate, it was washed three times with water and dried in a vacuum oven at 80 ° C for 24 h to obtain PAS-6pip. The chemical structure of the polymer was determined by NMR, IR, and UV characterization. Figure 2 As shown, the weight average molecular weight is 7.5×10 5 , wherein a is an integer of 0-10000, b is an integer of 0-200, and the polymerization mode of the groups in brackets corresponding to ab is random polymerization.
[0103] In order to facilitate the understanding of the synthesis process of the above-mentioned triazulene cross-linked poly 6-piperidinylazulene sulfide (b-PAS-6pip-3AzPh), the present application provides a synthesis route diagram of triazulene cross-linked poly 6-piperidinylazulene sulfide (b-PAS-6pip-3AzPh), as shown in Figure 2 As shown, Figure 2 This is a synthetic route diagram for triazulene cross-linked poly 6-piperidinylazulene sulfide (b-PAS-6pip-3AzPh) provided in this application.
[0104] (2) Preparation of triazulene cross-linked poly 6-piperidinylazulene sulfide anion exchange membrane:
[0105] b-PAS-6pip-3AzPh (1 g) was dissolved in 30 mL DMSO, and the polymer solution was filtered through a 0.45 μm polytetrafluoroethylene filter membrane, and the membrane solution was cast on a clean glass plate. Subsequently, the solution was evaporated at 80 ° C for 12 h, evaporated at 120 ° C for 12 h, and vacuum dried at 120 ° C for 24 h to completely remove the residual solvent. A dense I-type membrane was peeled off from the glass plate. In 1M KCl solution, ion exchange was performed at 80 ° C for 12 h, and then washed with deionized water 3 times to remove residual salts to obtain Cl - The membrane was placed in 1M KOH solution at 80°C for 12 h for ion exchange, and then washed three times with deionized water under nitrogen atmosphere to obtain OH - type membrane, namely b-PAS-6pip-3AzPh anion exchange membrane.
[0106] Example 3
[0107] This embodiment 3 provides a method for preparing a polyazulene sulfide anion exchange membrane, namely, a poly-6-piperidinylazulene sulfide (PAS-6pip) anion exchange membrane, and the specific steps are as follows:
[0108] (1) According to the literature method (Journal of Organic Chemistry 2019, 84(3), 1257-1275), the monomer 6-(N-piperidinyl)-1,3-dibromoazulene was prepared. Anhydrous Na2S (232 mg), 6-(N-piperidinyl)-1,3-dibromoazulene (1 g), and NaOH (20 mg) were weighed and placed in a reactor, and 20 mL of N-methylpyrrolidone (NMP) was added. The temperature was quickly raised to 200°C and the reaction was carried out for 6 h. After natural cooling, the mixture was washed with deionized water and anhydrous ethanol. The product obtained after filtration was vacuum dried at 80°C for 8 h. The dried product was a black solid powder, with a total weight of 0.7 g and a yield of 95%. 1 g of the product was dissolved in 30 mL of dimethyl sulfoxide (DMSO), and then K2CO3 (0.39 g) and iodomethane (1 mL) were added. The mixture was stirred at room temperature in the dark for 24 h. Ethyl acetate was added to the obtained viscous solution. The light yellow precipitate was filtered, washed with water three times, and dried in an oven at 80°C under vacuum for 24 h to obtain PAS-6pip. The chemical structure of the polymer was determined by NMR and IR characterization. Figure 3 As shown, the weight average molecular weight is 6.8×10 5 , wherein a is an integer of 0-10000, b is an integer of 0-200, and the polymerization mode of the groups in brackets corresponding to ab is random polymerization.
[0109] In order to facilitate the understanding of the synthesis process of the above-mentioned poly 6-piperidinylazulene sulfide (PAS-6pip), the present application provides a synthesis route diagram of poly 6-piperidinylazulene sulfide (PAS-6pip), such as Figure 3 As shown, Figure 3 The synthetic route diagram of poly 6-piperidinylazulene sulfide (PAS-6pip) provided in this application.
[0110] (2) Preparation of poly-6-piperidinazulene sulfide anion exchange membrane:
[0111] PAS-6pip (1 g) was dissolved in 30 mL DMSO, and the polymer solution was filtered through a 0.45 μm polytetrafluoroethylene filter membrane, and the membrane solution was cast on a clean glass plate. Subsequently, the solution was evaporated at 80 ° C for 12 h, evaporated at 120 ° C for 12 h, and vacuum dried at 120 ° C for 24 h to completely remove the residual solvent. A dense I-type membrane was peeled off from the glass plate. In 1M KCl solution, ion exchange was performed at 80 ° C for 12 h, and then washed with deionized water 3 times to remove residual salts and obtain Cl - The membrane was placed in 1M KOH solution at 80°C for 12 h for ion exchange, and then washed three times with deionized water under nitrogen atmosphere to obtain OH - type membrane, namely PAS-6pip anion exchange membrane.
[0112] In order to verify the performance of the polyazulene sulfide anion exchange membrane prepared in Examples 1-3, performance tests were performed on the polyazulene sulfide anion exchange membrane and a commercial FAA3-50 anion exchange membrane. The test results are shown in the figure.
[0113] The test results show that the b-PAS-6Pip-BiAz anion exchange membrane prepared in Example 1 has a thickness of 50±5 μm and an OH - The conductivity is 155mS / cm, the ion exchange capacity is 2.4mmol / g, the swelling rate is 35%, the tensile strength is 68MPa, the elongation at break is 13%, and the alkaline stability is maintained for 1000h at 80℃ and 1M KOH. The b-PAS-6pip-3AzPh anion exchange membrane prepared in Example 2 has a thickness of 50±5 microns and is stable at 80℃ and OH - The conductivity is 150mS / cm, the ion exchange capacity is 2.4mmol / g, the swelling rate is 46%, the tensile strength is 60MPa, the elongation at break is 13%, and the alkaline stability is maintained for 1000h at 80℃ and 1M KOH. - The conductivity is 144mS / cm, the ion exchange capacity is 2.4mmol / g, the swelling rate is 55%, the tensile strength is 43MPa, the elongation at break is 12%, and the alkaline stability is maintained for 1000h in 80°C and 1M KOH, indicating that the homogeneous anion exchange membrane prepared in this embodiment has small swelling, suitable ion conductivity and anion exchange capacity, and good mechanical properties; and with the addition of branched monomers, OH - The conductivity is increased, the swelling rate is reduced, and the mechanical properties are enhanced. At the same time, the polyazulene sulfide anion exchange membrane prepared in the example is superior to the commercial FAA3-50 anion exchange membrane in terms of conductivity and anion exchange membrane water electrolysis performance.
[0114] Figure 4 The polyazulene sulfide anion exchange membrane OH prepared in Examples 1, 2 and 3 - Conductivity test results. Figure 5 These are the anion exchange membrane water electrolysis test results of the polyazulene sulfide anion exchange membranes prepared in Examples 1, 2 and 3.
[0115] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A polyazulene sulfide anion exchange membrane, characterized in that: The polyazulene sulfide anion exchange membrane contains a polyazulene sulfide polymer, and the polyazulene sulfide polymer has at least one or two or more of the following structures: Wherein, R1 is a cationic group, R2 is a branching group, a is any integer between 1 and 10000 (preferably any integer between 1000 and 10000, more preferably any integer between 2000 and 10000), and b is any integer between 0 and 10000 (preferably any integer between 1 and 10000, more preferably any integer between 1 and 5000); The R1 is independently at least one or two or more of the following structures: Wherein, n is any integer between 1 and 100 (preferably any integer between 1 and 20, more preferably any integer between 2 and 10); The R2 is independently at least one or two or more of the following structures: In the above structure, the wavy line "﹏" represents the connection.
2. The ion exchange membrane according to claim 1, characterized in that Film thickness 10-200μm, The polymerization mode of the groups in brackets corresponding to a and b is random polymerization.
3. A method for preparing a polyazulene sulfide anion exchange membrane according to any one of claims 1 to 2, characterized in that: include: (1) Preparation of polyazulene sulfide polymer: Na2S, an azulene monomer A as shown in Formula 1, and a branched monomer R2-Br are placed in a reaction kettle, dissolved in a first organic solvent, heated, reacted, and then the solid product is washed, dried, and collected; the product is dissolved in a second organic solvent, potassium carbonate and iodomethane are added, reacted in the dark, and then ethyl acetate is added, purified, and the polyazulene sulfide polymer is collected; The specific structures of R1 and R2 are respectively the same as the corresponding R1 and R2 group structures in claim 1, One or more of the corresponding groups R1 and R2 structures in claim 1; (2) Preparation of polyazulene sulfide anion exchange membrane: The polyazulene sulfide polymer is dissolved in a second organic solvent to prepare a film, and then dried and collected. - type film, so that the I - Type membrane for ion exchange to obtain OH - type membrane, collecting polyazulene sulfide anion exchange membrane.
4. The method for preparing a polyazulene sulfide anion exchange membrane according to claim 3, characterized in that: The molar ratio of the sum of the added amounts of the azulene monomer and the branched monomer to the added amount of the Na2S in step (1) is 1:0.9-1.5 (preferably 1:0.9-1.2, more preferably 1:1.1), and the molar ratio of the added amounts of the branched monomer and the azulene monomer is 0-1:1 (preferably 0.05-0.5:1, more preferably 0.1-0.3:1).
5. The method for preparing a polyazulene sulfide anion exchange membrane according to claim 3, characterized in that: The reaction temperature is greater than 150° C. (preferably 150-220° C., more preferably 180-200° C.), and the reaction time is greater than 4 hours (preferably 4-24 hours, more preferably 6-10 hours).
6. The method for preparing a polyazulene sulfide anion exchange membrane according to claim 3, characterized in that: The first organic solvent is one or more of dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide, and the concentration of Na2S in the first organic solvent is 0.1-2 mol / L.
7. The method for preparing a polyazulene sulfide anion exchange membrane according to claim 3, characterized in that: The second organic solvent is one or more of acetonitrile, tetrahydrofuran, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide and sulfolane; The concentration of the product in step (1) in the second organic solvent is 0.1-1 g / mL, the final concentration of potassium carbonate is 1 mol / L, and the final concentration of methyl iodide is 1 g / mL.
8. Use of the polyazulene sulfide anion exchange membrane according to any one of claims 1 to 2, or the polyazulene sulfide anion exchange membrane prepared by the method according to any one of claims 3 to 7 as a diaphragm in an alkaline fuel cell or an alkaline electrolytic cell.
9. The use according to claim 8, characterized in that: The polyazulene sulfide anion exchange membrane has an OH content of 1.5447 W at 80°C. - The electrical conductivity is at least 100 mS / cm.
Citation Information
Patent Citations
Ion-conducting polymer, preparation method of ion-conducting cross-linked substance, anion-exchange membrane and application of anion-exchange membrane
CN117487052A
Azulenocyanine analogue compounds comprising anchoring group, method of making the same, and their use as dye for dye-sensitized solar cells
EP2700641A1
Process for producing thiabenzoazulene-propionic acid derivative
US20120123127A1